2016
DOI: 10.1093/infdis/jiw254
|View full text |Cite
|
Sign up to set email alerts
|

Ebola Virus Shedding and Transmission: Review of Current Evidence

Abstract: Background. The magnitude of the 2013-2016 Ebola virus disease outbreak in West Africa was unprecedented, with >28 500 reported cases and >11 000 deaths. Understanding the key elements of Ebola virus transmission is necessary to implement adequate infection prevention and control measures to protect healthcare workers and halt transmission in the community.Methods. We performed an extensive PubMed literature review encompassing the period from discovery of Ebola virus, in 1976, until 1 June 2016 to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(103 citation statements)
references
References 82 publications
4
98
0
1
Order By: Relevance
“…Our data here support attenuation rather than adaptation of EBOV-Makona during the recent epidemic, as lower organ titers and weaker disease progression in IFNAR −/− mice (Figures 2, 3, and S1) as well as slightly prolonged disease progression and reduced virulence in rhesus macaques (Figures 4, 5, and S2–S5) were associated with animals infected with EBOV-Makona later 2014 clinical isolates (Mali and Liberia). However, we did not observe any difference in viral shedding from mucosal membranes, commonly used as an indirect measure for transmission (Gustin et al, 2013; Vetter et al, 2016), when macaques were infected with EBOV-Makona early or later 2014 isolates or with EBOV-Mayinga (Figure S6). This is in contrast to a previous study describing increased virus shedding associated with EBOV-Makona (C05 and C07) infection when compared to EBOV-Kikwit (Wong et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…Our data here support attenuation rather than adaptation of EBOV-Makona during the recent epidemic, as lower organ titers and weaker disease progression in IFNAR −/− mice (Figures 2, 3, and S1) as well as slightly prolonged disease progression and reduced virulence in rhesus macaques (Figures 4, 5, and S2–S5) were associated with animals infected with EBOV-Makona later 2014 clinical isolates (Mali and Liberia). However, we did not observe any difference in viral shedding from mucosal membranes, commonly used as an indirect measure for transmission (Gustin et al, 2013; Vetter et al, 2016), when macaques were infected with EBOV-Makona early or later 2014 isolates or with EBOV-Mayinga (Figure S6). This is in contrast to a previous study describing increased virus shedding associated with EBOV-Makona (C05 and C07) infection when compared to EBOV-Kikwit (Wong et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…[33][34][35] Environmental contamination and survival Ebola virus has been isolated by cell culture from multiple body fluids of infected or convalescent patients including blood, saliva, stool, vaginal fluid, sweat, and urine for days or months after illness. 36 Given the high volume of diarrhea and vomiting and the potential for fomite transmission, the frequency of environmental contamination and survival of Ebola virus is of high concern. Several studies have assessed the frequency of contamination within the health care 37,39 or RT-PCR.…”
Section: Epidemiology and Transmissionmentioning
confidence: 99%
“…One study showed that a large community outbreak in SARS in Hong Kong could be explained by aerosol transmission (Yu et al, 2004), while another study showed that environmental surfaces in the hospitals could be contaminated with SARS-CoV and therefore contact transmission was considered possible (Dowell et al, 2004). It has been suggested that respiratory transmission of Ebola viruses could occur, although this is controversial (Osterholm et al, 2015;Vetter et al, 2016). Several experimental studies indicate that EBOV can be transmitted through aerosols in various animal species (Jaax et al, 1995;Weingartl et al, 2012).…”
Section: Aerosol and Droplet Transmission Of Respiratory And Enteric mentioning
confidence: 99%